2013
DOI: 10.1002/jgra.50132
|View full text |Cite
|
Sign up to set email alerts
|

Particle acceleration in dipolarization events

Abstract: [1] Using the electromagnetic fields of a recent MHD simulation of magnetotail reconnection, flow bursts and dipolarization, we investigate the acceleration of test particles (protons and electrons) to suprathermal energies, confirming and extending earlier results on acceleration mechanisms and sources. (Part of the new results have been reviewed recently in Birn et al., Space Science Reviews, 167, doi:10.1007/ s11214-012-9874-4.) The test particle simulations reproduce major features of energetic particle ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
205
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(223 citation statements)
references
References 71 publications
13
205
0
Order By: Relevance
“…In contrast to the high-shear case (Figure 2), the downward flow remains peaked near the center, although it splits up into several sites at later times. This is similar to the low-shear case, which has been studied more extensively in the context of the terrestrian magnetotail (e.g., Birn et al 2013Birn et al , 2014 and is therefore not shown here.…”
Section: Mhd Simulationssupporting
confidence: 67%
See 1 more Smart Citation
“…In contrast to the high-shear case (Figure 2), the downward flow remains peaked near the center, although it splits up into several sites at later times. This is similar to the low-shear case, which has been studied more extensively in the context of the terrestrian magnetotail (e.g., Birn et al 2013Birn et al , 2014 and is therefore not shown here.…”
Section: Mhd Simulationssupporting
confidence: 67%
“…Thus, the betatron and Fermi acceleration of the electrons in the collapsing field are equivalent to the gradient B and curvature drift components, respectively, antiparallel to the electric field (see, Northrop 1963;Birn et al 2013). These terms dominate the acceleration.…”
Section: Typical Orbits and Accelerationmentioning
confidence: 99%
“…The latter conclusion is supported strongly by test particle tracing in assumed or simulated propagating electromagnetic field pulses [Birn et al, 1997[Birn et al, , 1998[Birn et al, , 2004[Birn et al, , 2013[Birn et al, , 2014Li et al, 1998;Zaharia et al, 2000;Liu et al, 2009;Ashour-Abdalla et al, 2009Gabrielse et al, 2012;Pan et al, 2014aPan et al, , 2014b.…”
Section: Introductionmentioning
confidence: 84%
“…Using the three-dimensional time-dependent electric and magnetic field from magnetohydrodynamic (MHD) simulations of near-tail reconnection and flow bursts as basis for test particle studies, we have previously demonstrated major acceleration mechanisms and source regions and provided insights into spatial and temporal variations of electron and ion fluxes [Birn et al, 1997[Birn et al, , 2004[Birn et al, , 2013[Birn et al, , 2014. In addition to demonstrating that the major acceleration occurs in the v × B electric field associated with the dipolarization and flow…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the geospace environment once more, ion acceleration at dipolarization fronts in the geomagnetic tail has been studied, among others, by Ashour-Abdalla et al (2011), Ukhorskiy et al (2013), Birn and Hesse (2014), Greco et al (2014) and Greco et al (2015). Perri et al (2009) and Greco et al (2010) considered the combined effect of a steady-state dawn-dusk electric field and of stochastic Fermi acceleration due to the presence of transient magnetic structures: by performing a two-dimensional (2-D) test particle simulation, they showed that proton energies of up to 80-100 keV can be reached, in agreement with the above observations.…”
Section: Introductionmentioning
confidence: 99%